Joint Hypermobility Syndrome and Dysautonomia: Expanding Spectrum of Disease Presentation and Manifestation - Shomu Bohora (Indian Pacing and Electrophysiology Journal, 2010)
The varying clinical presentations of not so well recognized diseases, which continue to haunt patients is well described in the above quotes. Clinicians may not recognize associated subtle early presentations of the disease, till the disease has fully manifested itself. Of all the disorders of human body, autonomic syndromes are still the least understood. Presentation and association of autonomic diseases with other disorders may be so varied and subtle that clinicians may fail to recognize autonomic disturbance as an individual clinical entity within the disease and therefore appropriate management still remains inadequate. Similar association between joint hypermobility disorder, in which postural orthostatic tachycardia syndrome and dysautonomia is increasingly being recognized as an associated clinical entity, has been further elaborated.